Clarification of two taxon names of Phragmipedium (Orchidaceae, Cypripedioideae) - Mó, Edgar (2016)
Two subspecies of Phragmipedium humboldtii from Guatemala, P. humboldtii subsp. monstruosum and P. humboldtii subsp. triandrum (Orchidaceae, Cypripedioideae) were wrong published in Die Orchidee 66(3), 2015, since the new status of these subspecies are based on an incorrect name for the authorship of P. humboldtii (Warsz. ex Rchb.f.) J.T. Atwood & Dressler instead of P. humboldtii (Warsz.) J.T. Atwood & Dressler. The formal names of the subspecies are corrected here.